Pelvic radiography as a non-invasive screening tool for hiatal hernia in children with cerebral palsy. Issue 33 (19th August 2022) - Yoo, In Hyuk; Yang, Hye Ran
Abstract : The diagnosis of hiatal hernia (HH), causing severe gastroesophageal reflux disease and complications in children with cerebral palsy (CP) is cumbersome because invasive investigations are required for diagnosis. Hip displacement, one of the most common complications in children with CP, can be diagnosed with a simple pelvic radiograph. This study aimed to evaluate the association between the severity of hip displacement and HH and the diagnostic accuracy of Reimers' hip migration percentage (MP) on pelvic radiography in assessing the presence of HH. A total of 52 children with CP (27 boys, 25 girls; mean age, 6.3 years; range, 0.6–17.4 years) who underwent esophagogastroduodenoscopy, upper gastrointestinal series and pelvic radiography between March 2013 and February 2020 were recruited. Demographic and clinical characteristics, as well as endoscopic and radiological findings, were evaluated and statistically analyzed. HH was defined as ≥ 2 cm proximal displacement of the gastroesophageal junction identified in esophagogastroduodenoscopy or upper gastrointestinal series, and MP was calculated by evaluating the pelvic radiograph. Of the 52 children enrolled in this study, HH was diagnosed in 18 children (34.6%). When the patients were classified and analyzed according to the MP result, HH was observed in 10%, 26.7%, and 70.6% in MP <33%, MP 33%–39%, and MP > 40% groups, respectively ( P < .001). The optimal MP cutoff of 36.5% distinguished pediatric CP patients with HH from those without HH with a sensitivity of 78%, specificity of 68%, a positive predictive value of 56.0%, and a negative predictive value of 85.2%, respectively. The application of MP and the severity of hip displacement, which can be easily measured by simple radiography, may be useful and reliable in screening for detecting HH in children with CP. Retrospectively registered. This study was approved by the Institutional Review Board of Seoul National University Bundang Hospital (IRB No. B-2007-627-106).